Vision Screening of Ophthalmic Nursing Staff in a Tertiary Eye Care Hospital: Outcomes and ocular healthcare-seeking behaviours - Khan, Ruhi A. (Sultan Qaboos Univ Med J, 2017)
OBJECTIVES: This study aimed to evaluate ocular healthcare-seeking behaviours and vision screening outcomes of nursing staff at a tertiary eye care hospital. METHODS: This study was conducted between April and September 2016 among all 500 nurses employed at the King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia. Data were collected on age, gender, use of visual aids, the presence of diabetes, a history of refractive surgery and date of last ocular health check-up. Participants were tested using a handheld Spot(™) Vision Screener (Welch Allyn Inc., Skaneateles Falls, New York, USA). RESULTS: A total of 150 nurses participated in the study (response rate: 30.0%). The mean age was 41.2 ± 8.9 years old. Distance spectacles, reading spectacles and both types of spectacles were used by 37 (24.7%), 32 (21.3%) and 10 (6.7%) nurses, respectively. A total of 58 nurses (38.7%) failed the vision screening test. Visual defects were detected for the first time in 13 nurses (8.7%). With regards to regular eye checkups, 77 participants (51.3%) reported acceptable ocular healthcare-seeking behaviours; this factor was significantly associated with age and the use of visual aids (P <0.01 each). CONCLUSION: A high proportion of participants failed the vision screening tests and only half displayed good ocular healthcare-seeking behaviours. This is concerning as ophthalmic nurses are likely to face fewer barriers to eye care services than the general population.